1969
DOI: 10.1073/pnas.63.3.918
|View full text |Cite
|
Sign up to set email alerts
|

STIMULATION OF ANTERIOR PITUITARY ADENYL CYCLASE ACTIVITY AND ADENOSINE 3′:5′-CYCLIC PHOSPHATE BY HYPOTHALAMIC EXTRACT AND PROSTAGLANDIN E 1

Abstract: Abstract.-Hypothalamic extract, containing the releasing factors for anterior pituitary hormones, within minutes stimulated adenyl cyclase activity and adenosine 3' :5'-cyclic phosphate (cyAMP) concentrations in rat anterior pituitary in vitro. Cerebral cortical extract was ineffective and hypothalamic extract had no effect on these parameters in posterior pituitary or thyroid. Prostaglandin E1 also increased adenyl cyclase activity and cyAMP levels in anterior pituitary tissue. Although NaF augmented adenyl c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

1971
1971
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(22 citation statements)
references
References 18 publications
1
21
0
Order By: Relevance
“…Thus, we hypothesized that cAMP is an important chemical mediator, which, when present, dramatically increases the ability of sEHIs to reduce pain. Given that intracellular cAMP is increased by inflammation and is itself painful (17)(18)(19)(20), in the following experiments we used healthy rats without inflammation or neuropathy and monitored acute pain-related behavior measured as withdrawal responses to thermal and mechanical stimuli.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, we hypothesized that cAMP is an important chemical mediator, which, when present, dramatically increases the ability of sEHIs to reduce pain. Given that intracellular cAMP is increased by inflammation and is itself painful (17)(18)(19)(20), in the following experiments we used healthy rats without inflammation or neuropathy and monitored acute pain-related behavior measured as withdrawal responses to thermal and mechanical stimuli.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, a stimulatory effect of the N6-monobutyryl derivative and of various other derivatives of cAMI on the release of both LH and FSH from rat anterior pituitaries in vitro has been observed (G. Chavancy and F. Labrie, unpublished). Moreover, crude hypothalamic extracts stimulate adenohypophyseal adenylate cyclase activity and concomitant release of LH (20,21). However, definitive proof of the role of the adenylate cyclase system as mediator of the action of LH-releasing hormone/FSH-releasing hormone could be obtained only by measurements of adenohypophyseal adenylate cyclase activity or cAMP concentrations under the influence of the purified or synthetic neurohormone.…”
mentioning
confidence: 99%
“…While there is a general agreement that PGE increases pituitary cyclic AMP production [3,4,7,16] reports differ as to the effect of PGE on LH release. Makino [7] and Ratner et al [16] found increased LH release when PGE was added to incubated pituitaries, but other workers failed to find any increase in LH release after short [ 171 or long incubation periods with PGE ([ 181 and present results fig.1).…”
Section: Discussionmentioning
confidence: 99%
“…Crude hypothalamic extract containing LH-releasing activity was reported to stimulate adenylate cyclase and to increase the cyclic AMP level in the pituitary gland [3] . Recently it was found that synthetic LH-RH increased adenylate cyclase activity [4] cyclic AMP level and concomitantly stimulated LH release [S-8] .…”
Section: Introductionmentioning
confidence: 99%